Initiatives to Involve Women in Environmentally Friendly Economic Projects that Promote Sustainable Development in Iraq - Qasem, Nisreen Ghali (Journal of Asian Multicultural Research for Economy and Management Study, 2023)
Women have an important role in developing the economic sector around the world in general and Iraq in particular. Women have an important role in promoting the path of sustainable development and in building a next generation capable of creating decent work and developing other economic sectors. The research problem was crystallized by asking: What are the most important initiatives for economic projects that have participated? Where is the woman? To what extent are women empowered and what is their role in promoting sustainable development goals? The aim of the research was to know the extent of women’s empowerment and their role in environmentally friendly economic projects that enhance the path of sustainable development in Iraq, and to highlight the most important initiatives undertaken by the Central Bank of Iraq, the Ministry of Labor and Social Affairs, and the national strategy, and to update the weaknesses and strengths in economic projects that diminished the status of women. As for the research hypothesis, women play an important role in achieving the dimensions of sustainable development through financing and opportunities, while the most important conclusions were the weakness of the role of Iraqi women in the field of environmentally friendly economic projects, and if they exist, they are not at the level of ambition. The most important recommendations were to contain unemployment rates amongWomen in the government sector and the private sector through enhanced job opportunities for production and productivity and environmental, social and legal protection systems for women.